QSAR Study of Anthranilic Acid Sulfonamides as Inhibitors of Methionine Aminopeptidase-2 using different chemometrics tools - Pooria Zare; Maryam Sabet; Razieh Sabet (Shiraz University of Medical Sciences, 2023)
Quantitative structure activity relationships (QSAR) studies, as one of the most important areas in chemometrics, play a fundamental role in predicting the biological activity of new compounds and identifying ligand-receptor interactions. Quantitative relationships between molecular structure and methionine aminopeptidase-2 inhibitory activity of a series of anthranilic acid sulfonamides derivatives were discovered by different chemometrics tools including factor analysis based multiple linear regressions (FA-MLR), principale component regression analysis (PCRA) and genetic algorithm-partial least squares GA-PLS. The FA-MLR describes the effect of geometrical and quantum indices on enzyme inhibition activity of the studied molecules. The quality of PCRA equation is better than those derived from FA-MLR. GA-PLS analysis indicated that the topological (IC4 and MPC06), constitutional (nf) and geometrical (G (N..S)) parameters were the most significant parameters on methionine aminopeptidase-2 inhibitory activity. A comparison between the different statistical methods employed revealed that GA-PLS represented superior results and it could explain and predict 85% and 77% of variances in the pIC50 data, respectively.